Prognostic relevance of the HER2 status of circulating tumor cells in metastatic breast cancer patients screened for participation in the DETECT study program☆ - Müller, Volkmar; Banys-Paluchowski, M.; Friedl, T. W. P.; Fasching, P. A.; Schneeweiss, Andreas; Hartkopf, A.; Wallwiener, D.; Rack, B.; Meier-Stiegen, F.; Huober, J.; Rübner, M.; Hoffmann, O.; et al. (ESMO open, 2021)
Background - Circulating tumor cells (CTCs) have been reported to predict clinical outcome in metastatic breast cancer (MBC). Biology of CTCs may differ from that of the primary tumor and HER2-positive CTCs are found in some patients with HER2-negative tumors. - Patients and methods - Patients with HER2-negative MBC were screened for participation in DETECT III and IV trials before the initiation of a new line of therapy. Blood samples were analyzed using CELLSEARCH. CTCs were labeled with an anti-HER2 antibody and classified according to staining intensity (negative, weak, moderate, or strong staining). - Results - Screening blood samples were analyzed in 1933 patients with HER2-negative MBC. As many as 1217 out of the 1933 screened patients (63.0%) had ≥1 CTC per 7.5 ml blood; ≥5 CTCs were detected in 735 patients (38.0%; range 1-35 078 CTCs, median 8 CTCs). HER2 status of CTCs was assessed in 1159 CTC-positive patients; ≥1 CTC with strong HER2 staining was found in 174 (15.0%) patients. The proportion of CTCs with strong HER2 staining among all CTCs of an individual patient ranged between 0.06% and 100% (mean 15.8%). Patients with estrogen receptor (ER)- and progesterone receptor (PR)-positive tumors were more likely to harbor ≥1 CTC with strong HER2 staining. CTC status was significantly associated with overall survival (OS). Detection of ≥1 CTC with strong HER2 staining was associated with shorter OS [9.7 (7.1-12.3) versus 16.5 (14.9-18.1) months in patients with CTCs with negative-to-moderate HER2 staining only, P = 0.013]. In multivariate analysis, age, ER status, PR status, Eastern Cooperative Oncology Group performance status, therapy line, and CTC status independently predicted OS. - Conclusion - CTC detection in patients with HER2-negative disease is a strong prognostic factor. Presence of ≥1 CTC with strong HER2 staining was associated with shorter OS, supporting a biological role of HER2 expression on CTCs.
Gesehen am 20.12.2022